(untitled) (Nordic Journal of Practical Theology, 2025)
This article explores how Mark 10:13–16 acquires meaning as a liturgical text. The notion of the “liturgical biblical text” underscores that the text as rendered in the baptismal liturgy may be regarded as distinct from the text as it appears in the Bible. This distinction arises because the text is shaped through selective excerpts and paratexts, intertextual connections within the liturgy, and its ritual enactment. The study aims to investigate how the materiality of the context of use—in this case, the baptismal liturgy—configures both the biblical text and its interpretation. The research question is: In what ways does the baptismal liturgy shape Mark 10:13–16? The primary source material comprises the baptismal liturgies of the Church of Norway from the late nineteenth century to the present. The article demonstrates how Mark 10 acquires meaning through its interplay with Lutheran baptismal theology and the culturally established narrative of Jesus and the children, a dynamic that ultimately influences contemporary Bible translations.